2016
DOI: 10.4067/s0034-98872016000700003
|View full text |Cite
|
Sign up to set email alerts
|

¿Es eficiente la protección anti-radiación otorgada por gorros de pabellón de tungsteno-bismuto en cardiología intervencionista?

Abstract: (Rev Med Chile 2016; 144: 837-843)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
0
0
Order By: Relevance
“…When the attenuation value reported by the face mask is compared with the studies that evaluated the caps that used a lead equivalence level < 0.125, by Alazzoni et al 27 and Ramos-Avasola et al 28 , they reported an attenuation 65.8% and 40.2%, respectively; it can be seen that they are values similar to the 52% attenuation reported in the present investigation. The attenuation value of 52% achieved by the face mask may seem insufficient, but in Figure 1 it can be seen that the combined use of the face mask with the leaded acrylic suspended from the ceiling achieves an attenuation close to 100%, which shows how important it is to regularly use the acrylic screen in combination with the other radioprotective elements.…”
Section: Discussionsupporting
confidence: 83%
“…When the attenuation value reported by the face mask is compared with the studies that evaluated the caps that used a lead equivalence level < 0.125, by Alazzoni et al 27 and Ramos-Avasola et al 28 , they reported an attenuation 65.8% and 40.2%, respectively; it can be seen that they are values similar to the 52% attenuation reported in the present investigation. The attenuation value of 52% achieved by the face mask may seem insufficient, but in Figure 1 it can be seen that the combined use of the face mask with the leaded acrylic suspended from the ceiling achieves an attenuation close to 100%, which shows how important it is to regularly use the acrylic screen in combination with the other radioprotective elements.…”
Section: Discussionsupporting
confidence: 83%
“…Cuando se compara el valor de atenuación reportado por la máscara facial con los estudios que evaluaron los gorros que utilizaron un nivel de equivalencia con el plomo < 0,125, de Alazzoni et al 27 y Ramos-Avasola et al 28 , estos reportaron una atenuación del 65,8% y el 40,2%, respectivamente; se puede apreciar que son valores similares al 52% de atenuación reportado en la presente investigación. El valor de atenuación de un 52% logrado por la máscara facial quizás parezca insuficiente, pero en la figura 1 se puede apreciar que el uso combinado de la máscara facial con el acrílico plomado suspendido de techo logra una atenuación cercana al 100%, lo que pone de manifiesto lo importante que es el uso habitual de la pantalla acrílica en combinación con los demás elementos radioprotectores.…”
Section: Discussionunclassified
“…The bell cap, since it covers a larger area of the head, was the one that conferred the highest radioprotection, with an attenuation greater than 99%. This is probably explained by the fact that devices such as the bell cap and the lead face mask place a surface of attenuating material against the oblique radiation beams emerge from the interaction of the x-rays with the patient [28,34,41]. However, we must be careful in interpreting these results because the three studies 13,30,37 that evaluated them, combined the factors that showed the greatest attenuation and/or effectiveness of RAD found in this review, such as: a Pb equivalence of 0.5 mm, manufactured with Pb, and the dosimeters were placed inside and outside the cap, at the level of the head surface Therefore, the only way to know which of the factors mentioned above is the one that contributes more to radioprotection would be to perform a statistical analysis with metaregression models that would provide us with the induced contribution of the factors acting together, therefore this calculation reflects more faithfully the underlying truth of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%